Penyuluhan terhadap petani mengenai peningkatan pendapatan melalui produksi tanaman semusim tumpang sari di lahan jeruk belum menghasilkan di desa sawahan - Mira Yulianti; Hartoni Hartoni; Karimal Arum Shafriani (Jurnal Abdi Mas Adzkia, 2023)
Barito Kuala Regency is a tidal land area that has a superior horticultural commodity in the form of Siam Banjar oranges. But in the last year farmers have been flooded, resulting in a partially damaged citrus crop population, resulting in a decrease in income for farmers. In addition, in normal times the income of orange farmers is also uncertain, due to unstable fluctuations in orange prices. So it is necessary to carry out devotion that has an impact that can later increase the income of farmers. The method used in community service activities in Sawahan Village uses Participatory Action Research (PAR), with this method the role of community involvement is very large in identifying problems to solving problems and following up. The solution offered in this service, based on the problems identified is the extension of the intercropping plant system of chili with citrus plants. The results of existing conditions show that chili plants as intercropping plants with the suggested oranges can provide additional income for citrus farmers. The profit from chili plants which is an increase in the income of citrus farmers is IDR 1,558,028,-/wholesale/planting period. The response of the service participants gave a positive assessment of the technology presented, based on the results of the evaluation by judging from the responses of the participants based on the nature of innovation.